Unilateral plyometric training is superior to volume-matched bilateral training for improving strength, speed and power of lower limbs in preadolescent soccer athletes - Drouzas, V.; Katsikas, C.; Zafeiridis, A.; Jamurtas, A. Z.; Bogdanis, G. C. (Journal of Human Kinetics, 2020)
This study compared the effects of unilateral and bilateral plyometric training on strength, sprint performance and lower limb power. Sixty-eight preadolescent soccer athletes were randomly assigned to a unilateral plyometric training group (n=23), a bilateral plyometric training group (n=23) and a control group (n=22). Both plyometric training groups trained with equal volumes of unilateral or bilateral exercises for 15 minutes in each session, at which time the control group performed soccer-specific drills. Plyometric exercises were executed twice weekly for 10 weeks during the competitive season. The following tests were performed before and after the intervention: single-leg and double-leg countermovement jump, squat jump, horizontal jumps in different directions, maximal isometric strength of quadriceps and hamstrings, sprint performance, agility and balance. Unilateral plyometric training resulted in greater improvements compared to the control group in the following variables: hamstrings strength (ES: 0.91, p=0.037), 5m sprint time (ES: 0.93, p=0.004), single-leg countermovement jump (ES: 0.90, p=0.006), single- and double-leg squat jump (ES: 0.87, p=0.030 and ES: 0.73, p=0.067, respectively) and single-leg hop performance (ES: 1.01, p=0.004). The only tests where there was an improvement of BPT compared with the CG were the single-leg and double leg SJ (ES: 0.76, p=0.026; ES: 0.70, p=0.050). Quadriceps strength, side hop test, double-leg horizontal jump test, flamingo balance test and modified agility T-test were equally improved in all three groups (p<0.001). In conclusion, unilateral lower-limb plyometric training is more effective in increasing muscle strength and power in preadolescent soccer players when compared to bilateral training or soccer training alone.